2020
DOI: 10.1007/s10211-020-00351-w
|View full text |Cite
|
Sign up to set email alerts
|

An immune challenge of female great tits decreases offspring survival and has sex-specific effects on offspring body size

Abstract: Investment in immunity is expected to decrease (costly immunity) or enhance (terminal investment) reproductive performance. Here, we tested the effects of activation of the immune system in female great tits (Parus major) on (1) their reproductive effort and (2) the survival and body condition of their offspring, controlling for chick sex. We injected females tending 3-day-old chicks with sheep red blood cells (SRBC) or saline (control) and recorded their provisioning rates 6 days later, during the expected pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Although commonly mentioned in the literature, but rarely reported, we predict a significant increase of parasitemia in spring, illustrating spring recurrences (or spring relapses, Applegate, 1971). In light of the studies which showed a trade-off between activation of the great tit’s immune system and their reproduction (e.g., Ots & Hõrak, 1998; Grzędzicka, 2017; Kubacka & Cichoń, 2020), we predict a negative relationship between winter and/or spring parasitemia and reproductive success. Finally, in view of the energy expenditure associated with reproduction (Visser & Lessells, 2001; Nilsson & Råberg, 2001), we also predict that infected individuals who invest substantially in reproduction will later experience higher parasitemia (Hanssen et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…Although commonly mentioned in the literature, but rarely reported, we predict a significant increase of parasitemia in spring, illustrating spring recurrences (or spring relapses, Applegate, 1971). In light of the studies which showed a trade-off between activation of the great tit’s immune system and their reproduction (e.g., Ots & Hõrak, 1998; Grzędzicka, 2017; Kubacka & Cichoń, 2020), we predict a negative relationship between winter and/or spring parasitemia and reproductive success. Finally, in view of the energy expenditure associated with reproduction (Visser & Lessells, 2001; Nilsson & Råberg, 2001), we also predict that infected individuals who invest substantially in reproduction will later experience higher parasitemia (Hanssen et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…So, the larger size and the presumably greater energy demand during development may make males more sensitive to adverse environmental effects than females (Swenson 1986, Jones et al 2009, Rosivall et al 2010, Bouvier et al 2016). On the other hand, some studies did not find an influence of adverse conditions on sex-specific survival in great tits, for instance by increased pollution levels (in 15 days old nestlings; Eeva et al 2012), by increased competition among siblings (Nicolaus et al 2009) or by handicapping the parents (Kubacka and Cichoń 2020). These latter results suggest that male-biased offspring mortality may not be explained exclusively by higher sensitivity of male offspring to adverse environmental conditions.…”
Section: Sex Ratio Of Dead Offspringmentioning
confidence: 95%